Evidence that blood flukes (Trematoda: Aporocotylidae) of chondrichthyans infect bivalves as intermediate hosts: indications of an ancient diversification of the Schistosomatoidea. Issue 13 (November 2017) - Cribb, Thomas H.; Chick, Rowan C.; O'Connor, Wayne; O'Connor, Stephan; Johnson, Daniel; Sewell, Kim B.; Cutmore, Scott C.
Graphical abstract: Highlights: A new fish blood fluke (Aporocotylidae) cercaria is reported from a marine bivalve. A new aporocotylid is reported from a rhinobatid ray. These species form a clade with an aporocotylid from a holocephalan. Blood flukes from bivalve, gastropod and polychaete intermediate hosts form clades. If cophyly occurred, these blood fluke clades may have diversified over 400 million years ago. Abstract: Blood flukes (Aporocotylidae) of actinopterygians (bony fishes) have been shown to infect freshwater gastropods and marine polychaetes as intermediate hosts. However, no life cycle is known for any aporocotylid of chondrichthyans (cartilaginous fishes) and no adult aporocotylid has been linked to a cercaria infecting a bivalve. Here we report two novel infections that fill these gaps. Cercariae consistent with the family Aporocotylidae were found developing in sporocysts in the gonad of the surf pipi, Donax deltoides Lamarck, 1818 (Bivalvia: Donacidae), from Stockton Beach, central New South Wales, Australia. Adult aporocotylids were found in the heart of the giant shovelnose ray, Glaucostegus typus (Anonymous [Bennett], 1830), from Moreton Bay, southeastern Queensland, Australia. Phylogenetic analyses of the 28S rDNA region generated from the new specimens resulted in phylograms in which the two parasites form a strongly supported clade with Chimaerohemecus trondheimensis van der Land, 1967, the only aporocotylid known from a holocephalan and the only other chondrichthyan-infecting aporocotylid for which sequence data are available. Most marine aporocotylids of actinopterygians also form a strongly supported clade. These findings lead us to hypothesise that the aporocotylids of chondrichthyans are distinct from all other blood flukes in infecting bivalves as intermediate hosts. Putative cophyly between three major blood fluke clades and both definitive and intermediate host groups is consistent with diversification of the Schistosomatoidea over 400 million years ago.